Vzpostavljanje pogojev za partnersko sodelovanje z evropskimi knjižnicami - Jakac-Bizjak, Vilenka (Knjižnica, 2005)
An incidental survey of the annual reports of Slovenian libraries reveals that academic, university and special libraries are not participating in European projects advertised by the European Commission in its framework programs and co-financed through directorates covering separate expert fields, with the exception of one public library and the National and University Library. The purpose of the present article is to find out an answer to the question about the above described inactiveness of Slovenian academic, university and special libraries which do not take advantage of offered opportunities, and to discover reasons for it. Conditions under which academic, university and special libraries operate are described, as well as their effectiveness in following professional development and in the implementation of the accomplishments of library and information profession in their work-field. The mechanisms introduced by the Slovenian state for the measurement of the development of libraries and for the implementation of the provisions to ameliorate the conditions are described. Proposals for more active mutual participation and cooperation of Slovenian academic and special libraries at home and in the frames of Europe are presented.
Keywords: visokošolske knjižnice; specialne knjižnice; mednarodno sodelovanje; statistični podatki; Slovenia; Slovenija; Europe; Evropa